Implementasi Metode Waterfall Pada Sistem Informasi Pencarian Lowongan Kerja Berbasis Web - Praja Sendi Wardanu; Joko Aryanto (STMIK Budi Darma, 2023)
In the world of work that continues to develop, access to job vacancy information has become a very important aspect for society. Rapid technological advances have presented new challenges in terms of access to job vacancy information. Many people experience difficulties in finding work, especially due to limited access and costs associated with print media such as newspapers, brochures and magazines which were previously the main source of employment information. This website aims to make it easier for job seekers to get access to various job vacancies online. To achieve this goal, the research uses quantitative research methodology, including literature studies to understand concepts and user needs, observations to observe current job search methods, interviews with potential job seekers to collect relevant data and questionnaires to obtain relevant data from applicants and applicants. public. Meanwhile, in creating the system, the System Development Life Cycle (SDLC) methodology with a waterfall model approach was used, and Unified Modeling Language (UML) was used as a tool to describe the resulting system. The reason for using the waterfall method for developing a website-based information system is to facilitate job seekers' access to job vacancy information. This approach provides a structured framework, enables planning from analysis to implementation, and emphasizes strong documentation to ensure a comprehensive understanding of user needs and an end result that meets expectations. The research results obtained showed that of the 25 respondents, the percentage level of acceptance by the public or applicants for the system being developed was the highest in the first statement, namely 40% agreed, the second was 36% neutral and the third was 40% agreed. Through this website-based information system, research concludes that the reduction in costs and time for people looking for work is very significant and effective. Positive impacts include the potential to reduce unemployment rates and increase inclusivity, provide wider job access opportunities, and create a better world of work